The Political Debate on Climate Change in Italy: A Discourse Network Analysis - Ghinoi, Stefano (2020)
Climate change is considered by policymakers as one of the most pressing global issues of our time. International institutions and national governments are, to varying degrees, committed to tackling climate change, but it has only been possible to define a shared system of collective goals across countries through the 2015 United Nations Climate Change Conference in Paris (COP21). A growing interest in climate change policy has been present in the Italian political debate, yet we have little evidence regarding the nature of related climate change debates across Italian policymakers. By using Discourse Network Analysis (DNA) to investigate Italian policymakers’ discourses in the Chamber of Deputies during the 17th Italian Legislature (2013–2018), this study shows that debates on climate change-related strategies are largely unpolarized, except for certain issues, and that coalitions emerge over time around core strategies. Groups of policymakers with similar policy beliefs emerge independently from their political affiliations. Our analysis is thus the first to apply DNA to provide empirical evidence of the convergence across Italian policymakers and the potential for the bridging of political discourses on climate change.